Evaluating the Influence of COVID-19 Among Dental Practitioners After Lockdown - Eisha Abrar BDS; Adel S. Abduljabbar PhD; Mustafa Naseem MSc; Maryam Panhwar BDS; Fahim Vohra PhD, MProsRCS; Tariq Abduljabbar DMSc (SAGE Publishing, 2021)
Clinical activities at dental premises after the COVID-19 lockdown period or post-COVID-19 are likely to be a challenge for all practicing dentists. To assess the impact of the COVID-19 pandemic on dentists and change in dental practice following lockdown, a total of 1150 participants were approached through online survey forms registered on www.surveys.google . A link containing details of the questionnaire and a consent form was sent to dentists through emails and social media forums. The questionnaire included 3 domains comprising of seventeen questions. The first section focused on demographics. The second section inquired about the change in dental practice, that is, clinical hours, use of PPE, type of treatment, and patient flow. The third section investigated the impact of COVID-19 on dentistry. Means, standard deviation, and percentages were calculated using descriptive statistics. Chi-square was used to find an association between different variables. The response rate was 87%. Demographic factors revealed participants aged from 20.45 to 40.55 years. The data showed around 89.6% (896) of dentists have altered their clinical working hours post lockdown and, approximately, 59.7% (597) of dentists provided only emergency treatments. 88.1% (881) of the dentists wore PPE during dental procedures. Overall, a huge negative impact of the COVID-19 pandemic was observed among practicing dentists in terms of the dental supply chain, cost, and availability of dental equipment, treatment cost, and bill payments.COVID-19 pandemic compromised dental care. Though dentists were taking precautionary measures and have changed their practice according to the guidelines provided by the ADA and World Health Organization, they were still experiencing monetary loss due to decrease patient influx post lockdown.